2016
DOI: 10.1080/14992027.2016.1177215
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress biomarkers and otoacoustic emissions in humans exposed to styrene and noise

Abstract: Exposure-induced damage of the cochlear amplifier is shown in the mid-frequency range, confirming animal experiments, in which hair cells in the cochlear middle turn were damaged. Hearing damage is consistent with the outer hair cell apoptosis pathway associated with oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
(41 reference statements)
2
10
0
Order By: Relevance
“…A relationship between styrene metabolites and oxidation products was only observed for the RNA oxidation product oxoGuo in non-smokers. However, a significant negative relationship was reported for oxoGuo and DPOAE components at specific frequencies (Sisto et al 2016). The authors interpreted this study as supporting the mechanistic hypothesis of styrene-induced damage of the cochlear amplifier in the mid-frequency range, consistent with OHC apoptosis associated with oxidative stress.…”
Section: Non-cancer Health Effectssupporting
confidence: 73%
See 3 more Smart Citations
“…A relationship between styrene metabolites and oxidation products was only observed for the RNA oxidation product oxoGuo in non-smokers. However, a significant negative relationship was reported for oxoGuo and DPOAE components at specific frequencies (Sisto et al 2016). The authors interpreted this study as supporting the mechanistic hypothesis of styrene-induced damage of the cochlear amplifier in the mid-frequency range, consistent with OHC apoptosis associated with oxidative stress.…”
Section: Non-cancer Health Effectssupporting
confidence: 73%
“…Oxidative stress biomarkers have recently been associated with sensitive indices of hearing impairment in solventexposed workers. As discussed previously, workers in an FRP facility exposed to mean styrene concentrations of about 26.5 ppm (and noise levels of 82 dB) exhibited reduced amplitude of total DPOAEs in the mid-frequency range compared to age-and sexmatched controls said to have no exposure to solvents, noise, or other ototoxic agents (Sisto et al 2016). Urinary concentrations of MA + PGA and the DNA and RNA oxidation products 8-oxo-7,8-dihydroguanine (oxoGua), 8-oxo-7,8-dihydro-20-deoxyguanosine (oxodGuo), and 8-oxo-7,8-dihydroguanosine (oxoGuo) were measured in the exposed workers.…”
Section: Non-cancer Health Effectsmentioning
confidence: 67%
See 2 more Smart Citations
“…It should be emphasized that aging is the most common reason for sensorineural and noise-induced hearing abnormalities, and both related closely with the formation of ROS (reactive oxygen species). Researchers suggested that hearing damage is associated with the outer hair cell apoptosis pathway which due to oxidative stress involving oxidative damage to biological molecular (such as nucleic acids, lipids, proteins and so on) and accompanies progression of several physical conditions, including neurodegenerative, cardiovascular, eproductive and kidney diseases, and also different cancers 32 .…”
Section: Discussionmentioning
confidence: 99%